Antifungal activity of endophytic fungi extracts isolated from Vitellaria paradoxa against phytopathogenic fungi in cucumber crops - Mohammed, Abdullahi Mairiga; Umar, Kabir Mustapha; Abdullahi, Ibrahim Lawal; Terhem, Razak (Update Publishing House, 2025)
This study assessed the antifungal activity of crude extracts from endophytic fungi isolated from Vitellaria paradoxa against Fusarium oxysporum, F. solani, F. demerum, F. cladosporum, Aspergillus niger, and A. flavus associated with cucumber plants. Morphological and molecular methods identified three suspected endophytes (MIK1, MIK2, and MIK3) as A. niger, A. welwitschiae and Rhizopus arrhizus. The endophyte culture broths were incubated on an orbital shaker for 14 days at 28 °C and 120 rpm and then extracted with organic solvents. The ethyl acetate yielded (4.57 g), methanol (4.18 g), and n-hexane (3.68 g) crude extracts. The fungal endophytes (MIK1, MIK2, and MIK3) were screened for their antagonistic activity against six pathogenic fungi using a dual culture method. The results show that all the endophytes strongly inhibit the growth of fungi, with inhibition rates of 92% and 99%. The antifungal activity of the crude extracts was tested using the poisoned food technique at concentrations of 0.25, 0.50, 1.0, 1.5, and 2.0 μg/mL. The results indicate that the ethyl acetate extract of A. niger exhibits potent inhibition against the growth of the same fungus, with inhibition rates of 78.18% and 79.12% at 2.0 μg/mL. All the fungal crude extracts possess antifungal activity and can be used to manage the six fungal species tested. Further field experiments should be conducted for practical applications against other plant pathogens to reduce reliance on synthetic agrochemicals.